2020
DOI: 10.7717/peerj.8664
|View full text |Cite
|
Sign up to set email alerts
|

The altered gut microbiota of high-purine-induced hyperuricemia rats and its correlation with hyperuricemia

Abstract: Some studies on the hyperuricemia (HUA) have focused on intestinal bacteria. To better understand the correlation between gut microbiota and HUA, we established a HUA rat model with high-purine diet, and used 16S rRNA genes sequencing to analyze gut microbiota changes in HUA rats. To analyze the potential role played by gut microbiota in HUA, we altered the gut microbiota of HUA rats with antibiotics, and compared the degree of uric acid elevation between HUA and antibiotic-fed HUA rats (Ab+HUA). Finally, we e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
92
1
2

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 62 publications
(103 citation statements)
references
References 32 publications
5
92
1
2
Order By: Relevance
“…In recent years, many studies have found that the intestinal flora of patients with hyperuricemia is different from that of normal people. Compared with the intestinal flora of healthy people, hyperuricemia patients have a flora disorder, mainly manifested in the decrease of the number of Lactobacillus , while the number of Bacillus , Escherichia coli , and total aerobic bacteria increased [ 32 , 33 ]. Xanthine oxidase plays an important role in the formation of uric acid.…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, many studies have found that the intestinal flora of patients with hyperuricemia is different from that of normal people. Compared with the intestinal flora of healthy people, hyperuricemia patients have a flora disorder, mainly manifested in the decrease of the number of Lactobacillus , while the number of Bacillus , Escherichia coli , and total aerobic bacteria increased [ 32 , 33 ]. Xanthine oxidase plays an important role in the formation of uric acid.…”
Section: Discussionmentioning
confidence: 99%
“…The gut microbiota regulates the metabolism of glucolipids ( Yin et al., 2018 ), amino acids ( Kawase et al., 2017 ; Zhang et al., 2020 ), vitamins ( Caesar, 2019 ), bile acids ( RamĂ­rez-PĂ©rez et al., 2018 ), and other nutrients ( Pathak et al., 2020 ) through the microbiota–gut–brain axis ( Carabotti et al., 2015 ). Conversely, the dysbiosis of gut microbiota leads to metabolic diseases, such as obesity, cardiovascular disease (hyperlipidemia, atherosclerosis and hypertension), insulin resistance, type 2 diabetes, gout, and hyperuricemia ( Fan et al., 2018 ; Liu et al., 2020 ; Mandal and Mount, 2015 ; Mendes-Soares et al., 2019 ; Novoseletskyi, 2013 ). Fortunately, the homeostasis of gut microbiota can be manipulated by diet, faecal microbiota transplantation, and other approaches ( Fuentes et al., 2017 ; Kelly et al., 2014 ; Liu et al., 2017 ; Lee et al., 2019 ; Thomas and Versalovic, 2010 ).…”
Section: Introductionmentioning
confidence: 99%
“…Gouty arthritis is a chronic inflammatory joint disease that results from imbalanced purine metabolism in the human host. Recent findings that the gut microbiota are perturbed by gout disease (30,(32)(33)(34)(35)(36) xanthine), foods rich in hypoxanthine such as animal and fish meats have been reported to be more strongly associated with gout development (50). This uric acid precursor was elevated in the low All rights reserved.…”
Section: Discussionmentioning
confidence: 99%
“…The copyright holder for this preprint this version posted September 3, 2020. ; https://doi.org/10.1101/2020.09.02.20187013 doi: medRxiv preprint and murine models (32)(33)(34)(35) correlated changes in gut microbiota composition to the presence of gout disease, suggesting that microbiota properties could be used to monitor disease development, progression and recovery. Several of these 16S-based studies have been combined with gene catalog (36) and metabolomic (29) analyses to better understand the metabolic changes that accompanied compositional dysbiosis.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation